Content of Pocess of Self- Education of Students as a Pedagogical Problem - N. M. Romanenko (Vestnik MGIMO-Universiteta)
The article considers methodological problems of the content of process of self-education of students as a pedagogical problem showing the specifics of teaching activities in institutions of higher education. The author analyzes the category "selfeducation of students" is analyzed in the works of different authors of the Soviet and post-Soviet period and stresses the peculiarities of students self-education with reference to their age and stage of learning in the higher school. The article stresses the significance of information and communication technologies (ICT) in the course of building self-educational skills of university students.